Calcified abdominal pregnancy with eight years of evolution - Rahman, Md Masudur; Quddush, ASM Ruhul; Islam, Mahzabeen; Sen, Shila; Jahan, Akhter; Begum, Ferdusi; Bousrleea, Reeva Aireen; Rayen, Junnu (Community Based Medical Journal, 2013)
The lithopedion (Calcified abdominal pregnancy) is a rare phenomenon and there are less than 300 cases reported in the medical literature.In this case, a 35 year-old patient had her third pregnancy 8 years earlier without medical assistance since then she came to our hospital with low back pain. Complementary examinations (Abdominal X-ray, Ultrasonography and Color Doppler Ultrasonography) demonstrated an extra uterine abdominal about 25 - week pregnancy with calcified areas. Exploratory Laparatomy was performed, with extirpation of a well - conserved fetus with non calcified ovular membrane. DOI: http://dx.doi.org/10.3329/cbmj.v1i1.13852 Community Based Medical Journal Vol.1(1) 2012 33-34